Windshear Identification Algorithms by Doppler Pulse Lidar - Baranov Nikolay; Lemishchenko Ekaterina (ITM Web of Conferences, 2019)
Doppler pulse lidars are increasingly common as a tool for monitoring hazardous wind phenomena. Possible applications include measurements of wake vortices behind aircraft, detection of vertical and horizontal wind shear, detection of gust fronts, and identification of areas of intense turbulence. This paper reviews several computational procedures used to measure wind shear parameters and determine the gust front position. Algorithms for wind shear calculation are based on the construction of regression dependencies of changes in the wind speed components at a given distance. In accordance with the ICAO recommendations, horizontal wind shear is determined at a distance of 600m. The application of the algorithms is illustrated by the results of data processing for scanning in PPI mode performed by WINDEX-5000 Doppler pulse lidar.